May 14, 2023 Political Impact and Importance of Türkiye’s Presidential Election Abroad (London Journal of Research In Humanities and Social Sciences, 2023)
According to the system of government in Türkiye, the president is the head of the state and the highest and most authorized person who shows his or her activities in legislative, executive, and judicial proceedings according to the constitution. In Turkish history, as of July 9, 2018, the parliamentary system was abolished and the presidential system was officially put into practice. On May 14, 2023, parliamentary elections and presidential elections will be held in Türkiye. In this year’s elections, which take place every five years, the thirteenth president and the twenty-eighth term deputies will be announced. The presidential candidates are Recep Tayyip Erdoğan, Kemal Kılıçdaroğlu, Muharrem İnce and Sinan Oğan. These elections in Türkiye do not only have an impact within the country but also attract the attention of other countries because of the country’s geographic location and its international relations with other part of the world. The purpose of this paper is to understand the meaning and importance of the 2023 elections in Türkiye in the international dimension and to examine the political significance of the elections in foreign countries in an unbiased manner.
Keywords: türkiye’s election; erdoğan; may 14